2022
DOI: 10.1186/s13765-021-00664-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bacteriocin-producing Bacillus strains on quality characteristics of fermented soybean product with biogenic amine-forming lactic acid bacteria

Abstract: This study evaluated the antibacterial activity of bacteriocin produced by Bacillus strains against biogenic amines (BA)-forming lactic acid bacteria (LAB), and the applicability of desirable strains as Bacillus starters for safety and quality improvement of fermented soybean products. The BA-forming ability of the tested LAB in amino acid decarboxylase broth was mostly strain specific rather that species specific. The bacteriocin produced by specific Bacillus strains: Bacillus sp. DB407, Bacillus licheniformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Tyramine contents in Cheonggukjang could be reduced by adding nicotinic acid ( Kang et al, 2018 ), and a lower fermentation temperature (25 °C compared to generally 37 °C) may decrease tyramine formation ( Park et al, 2020 ). Furthermore, Lim (2022) suggested that B. subtilis starter could decrease the accumulation of cadaverine, tryptamine, and tyramine. Although researchers have investigated the effect of the cultivar on biological activities ( Kim et al, 2012 ), volatile compound profiles ( Cho et al, 2017 ), and free amino acids (FAAs) profiles ( Kim et al, 2012 ) of Cheonggukjang , there has been no research reported regarding the influence of soybean cultivar on BAs formation in Cheonggukjang .…”
Section: Introductionmentioning
confidence: 99%
“…Tyramine contents in Cheonggukjang could be reduced by adding nicotinic acid ( Kang et al, 2018 ), and a lower fermentation temperature (25 °C compared to generally 37 °C) may decrease tyramine formation ( Park et al, 2020 ). Furthermore, Lim (2022) suggested that B. subtilis starter could decrease the accumulation of cadaverine, tryptamine, and tyramine. Although researchers have investigated the effect of the cultivar on biological activities ( Kim et al, 2012 ), volatile compound profiles ( Cho et al, 2017 ), and free amino acids (FAAs) profiles ( Kim et al, 2012 ) of Cheonggukjang , there has been no research reported regarding the influence of soybean cultivar on BAs formation in Cheonggukjang .…”
Section: Introductionmentioning
confidence: 99%
“…There are many kinds of bacteriocins classified by their amino acid sequences, mechanism of action, and secretion mechanism [8]. Moreover, their production depends on their strain and culture optimization [9].…”
Section: Introductionmentioning
confidence: 99%